Language Across the Curriculum & CLIL in English as an Additional Language (EAL) Contexts - Lin, Angel M.Y. (Springer, 2016)
Language Across the Curriculum (LAC) and Content and Language Integrated Learning (CLIL) constitute rapidly growing areas of both research and practice in many parts of the world, especially in Asia, Australia and Europe. In recent years, LAC and CLIL are gaining intense attention particularly in contexts where English is learnt as a foreign language or as an additional language (EAL). The global spread of English has arisen from a whole host of historical, political and socio-economic factors.
Theory and Practice